Pengaruh Sistem Pengendalian Internal dan Kompetensi Perangkat Desa Terhadap Kepatuhan Wajib Pajak dengan Kesadaran Wajib Pajak Sebagai Variabel Intervening di Pemerintah Desa Kecamatan Kabila Bone - Fadila Rahmawaty Biahimo; Usman Usman; Ayu Rakhma Wuryandini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to analyze the effect of the internal control system and village apparatus competence on taxpayer compliance, with taxpayer awareness as an intervening variable in village governments in Kabila Bone District, Bone Bolango Regency. This research employed a quantitative approach focusing on internal control systems, village apparatus competence, taxpayer awareness, and taxpayer compliance. The background of this study is the low level of land and building tax (PBB) compliance, inaccuracies in tax object data, and delays in village fund disbursement due to the suboptimal realization of PBB payments. The results indicate that the internal control system does not have a significant direct effect on taxpayer compliance. However, village apparatus competence has a positive and significant effect on taxpayer compliance. In addition, taxpayer awareness has been proven to positively and significantly affect taxpayer compliance. This study also found that the internal control system and village apparatus competence positively influence taxpayer awareness. Furthermore, taxpayer awareness is able to mediate the effect of the internal control system and village apparatus competence on taxpayer compliance. These findings indicate that improving taxpayer compliance is not only influenced by a strong internal control system, but also highly dependent on the competence of village officials and increased public awareness in fulfilling tax obligations.